2019
DOI: 10.1002/btm2.10138
|View full text |Cite
|
Sign up to set email alerts
|

Leader cell PLCγ1 activation during keratinocyte collective migration is induced by EGFR localization and clustering

Abstract: Re‐epithelialization is a critical step in wound healing and results from the collective migration of keratinocytes. Previous work demonstrated that immobilized, but not soluble, epidermal growth factor (EGF) resulted in leader cell‐specific activation of phospholipase C gamma 1 (PLCγ1) in HaCaT keratinocytes, and that this PLCγ1 activation was necessary to drive persistent cell migration. To determine the mechanism responsible for wound edge‐localized PLCγ1 activation, we examined differences in cell area, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While coordinated directionality refers to how cohesively cells migrate in a similar direction, directional persistence refers to the directed migration of individual cells or, more simply, how straight individual cell trajectories are. Notably, these two elements are often seen to co-occur in monolayers which show increased wound closure efficiency [ 46 ]. The directional persistence of a cell can be quantified by measuring the velocity autocorrelation of cell trajectories [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…While coordinated directionality refers to how cohesively cells migrate in a similar direction, directional persistence refers to the directed migration of individual cells or, more simply, how straight individual cell trajectories are. Notably, these two elements are often seen to co-occur in monolayers which show increased wound closure efficiency [ 46 ]. The directional persistence of a cell can be quantified by measuring the velocity autocorrelation of cell trajectories [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…While coordinated directionality refers to how cohesively cells migrate in a similar direction, directional persistence refers to the directed migration of individual cells or, more simply, how straight individual cell trajectories are. Notably, these two elements are often seen to co-occur in monolayers which show increased wound closure efficiency ( Kim et al (2019 )). The directional persistence of a cell can be quantified by measuring the velocity autocorrelation of cell trajectories ( Gorelik and Gautreau (2014 )).…”
Section: Resultsmentioning
confidence: 99%
“…We further analyzed the potential mechanism behind hADSC functions in SW-treated wounds. Previous literature has shown that wound repair is closely related to the EGF pathway [24], so we hypothesized that hADSCs induce proliferation and migration of wound repair The number and proportion of proliferating cells or skin stem cells in the control group and the SW+hADSC group were significantly higher than those in the SW group. Scale bars indicate 100 μm.…”
Section: Hadscs Affect Mek/erk Signaling Pathway Activationmentioning
confidence: 95%